Training Specialists in the Field of Innovative Financial Technologies in Russia - A. A. Tsyganov; S. V. Brovchak; Yu. A. Gorelova; L. S. Krutova (Высшее образование в России)
Formation of educational programs for new types of activity is a complex task that should be solved on the basis of interaction between educational institutions and the professional community, assessment of the current market demand for specialists with certain competencies. But the task becomes much more complicated if the need for specialists is growing rapidly, and the community of professionals is just being formed and cannot have the proper impact on the educational services market. In this case, the educational infrastructure, under certain conditions, can become a controlling component of market development, but it can also become a factor in false goal-setting and inhibition of development.The popularity of financial technologies among the population and applicants prompts higher educational institutions to form educational programs, which are often criticized, and graduates do not always gain employment in accordance with their diploma qualifications. There is a contradiction between the expectations of the labor market, which have not yet been formalized, and the supply from Russian educational institutions.Purpose. The article aims to formulate proposals for the standardization of requirements for specialists in innovative financial technologies (FinTech) based on the consolidation and analysis of the opinions of companies professionally involved in FinTech. Research methods. The authors applied generalization and empirical research methods such as selective market research, statistical observation. Results. The results of an empirical study on the existing educational programs in the sphere of financial technology (Fintech) are presented. Scientific novelty. It is shown that in the conditions of an underdeveloped market and the initial stage of a professional community development, educational infrastructure can become a tool for market development based on a common understanding and standardization of educational competencies and programming of its further development. Practical significance. Taking into account the results obtained, conclusions were formulated that make it possible to substantiate the need to introduce an independent assessment of the formed qualifications into the educational process.